Donor human milk practice in Indonesia: a media content analysis - Pramono, Andini; Hikmawati, Alvia (Frontiers in Nutrition, 2024)
The donor human milk is recommended as the second-best alternative of supplementation when the mother is unable to breastfeed directly, however little is known about the experience of mothers, families in the communities regarding accessing and donating expressed breastmilk in Indonesia. This study aims to identify the experience of donor human milk in the society in Indonesia. Method: search was conducted through six main online news portals. Keywords used include "donor human milk", "expressed breastmilk" and "wet nursing" in Bahasa Indonesia. 107 articles were found, and only 20 articles were included for analysis using qualitative media content analysis approach. Results: Five themes were identified: 1) The whys and wherefores of donor human milk, 2) National and religious-based regulations, 3) Recommendations from authorized organizations, healthcare professionals and Islamic scholar, 4) Negative impact from lack of national regulation, and 5) Contradict feelings of mothers. With the lack of detailed information on how to access or donate expressed human milk and no human milk bank in place, informal human milk sharing is inevitably occurring in the community. This also has been a concern for authorized organizations, healthcare professionals and Islamic scholar. Consequently, there are negative impacts experienced by mothers, both the donor and recipient, including contradicting feelings. Engaging with Islamic scholar and health care professionals to develop a clear guidelines and regulations to enable mothers and families access and/or contribute to DHM in a safe and accountable way is critical to prevent further problems occurring in the Indonesian society. We searched through six main online news portals in Indonesia (Kompas.com, tempo.co, antaranews.com, detik.com, cnbcindonesia.com and cnnindonesia.com) on 29-30 January 2024. Keywords used including "breastmilk donor", "expressed breastmilk" and "wet nursing" in Indonesian language. This term is defined as expressed breastmilk that is donated by a mother